Two new species of Munidopsis (Crustacea: Anomura: Munidopsidae) from the Kermadec and Louisville ridge systems off New Zealand - Schnabel, Kareen E.; Ahyong, Shane T. (Zootaxa, 2015)
Two new species of Munidopsis are described from the wider New Zealand region. Munidopsis bamberi sp. nov. is described from the Havre Trough adjacent to the Kermadec Volcanic Arc north-east of the New Zealand continental shelf, and is named in honour of Roger Bamber for his contributions to arthropod taxonomy and systematics. The second species is M. sculpo sp. nov. from Forde Seamount on the Louisville Ridge east of New Zealand. This brings the number of Munidopsis species known in New Zealand waters to 17 and a key to the New Zealand species is provided.